Posttransplantation Hypomagnesemia as a Predictor of Better Graft Function after Transplantation - Tammy Hod; Ofer Isakov; Bhanu K. Patibandla; Kenneth B. Christopher; Rami Hershkoviz; Idit F. Schwartz; Anil Chandraker (Karger Publishers, 2020)
Background: Hypomagnesemia is frequently seen after transplantation and is particularly associated with the use of calcineurin inhibitors (CNIs). Methods: We conducted a retrospective, single-center analysis (2000-2013, N = 726) to explore the relationship between hypomagnesemia and long-term allograft outcome in kidney transplant recipients. For this study, a median serum magnesium (Mg) level of all measured Mg levels from 1 month to 1 year after renal transplantation was calculated. Results: For every increase in Mg by 0.1 mg/dL, the GFR decreased by 1.1 mL/min at 3 years posttransplant (p < 0.01) and by 1.5 mL/min at 5 years posttransplant. A median blood Mg level of ≥1.7 was found to be an independent predictor of a GFR <60 mL/min at 3 years posttransplant. The odds of having a GFR <60 mL/min 3 years posttransplant was almost 2-fold higher in the high Mg group than in the low Mg group. Conclusions: Hypomagnesemia from 1 to 12 months after renal transplantation is associated with a better allograft function up to 5 years posttransplant. This relationship was found to hold true after accounting for baseline allograft function and the presence of slow graft function.